2020
DOI: 10.1182/blood-2020-142142
|View full text |Cite
|
Sign up to set email alerts
|

Novel BCR-ABL1 Tyrosine Kinase Inhibitor (TKI) HQP1351 (Olverembatinib) Is Efficacious and Well Tolerated in Patients with T315I-Mutated Chronic Myeloid Leukemia (CML): Results of Pivotal (Phase II) Trials

Abstract: INTRODUCTION HQP1351 (olverembatinib) is an orally active third-generation BCR-ABL TKI designed for treatment of the patients with CML, harboring T315I mutation, which confers resistance against all first- and second-generation TKIs. METHODS The TKI resistant CML patients harboring T315I mutations either in chronic-phase (CP), or in accelerated-phase (AP), were enrolled into two single-arm, multicenter, open-label pivotal studies: HQP1351-CC201 in and HQP1351-CC202,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…The CCyR rate ranged from 16.1% with omacetaxine to 64.8% with ponatinib at 6 months, and the corresponding values at 12 months were 16.2% to as high as 83.9% with bosutinib. 28–31 Among the included interventions, the CCyR rates ranged from 38.7% at 6 months to 66% at 10.2 months for asciminib, 20,32 16.2% at 12 months to 83.9% at 12 months for bosutinib, 30,31 6% at 15 months to 69.6% at 40.8 months for ponatinib, 33,34 4% at 19.1 months to 16.1% at 6 months for omacetaxine, 28,35 36.8% at 12.8 months to 65.9 at 7.9 months for olverembatinib, 36,37 24% at 12 months to 31% at 16 months for nilotinib, 19,38 and 11% at 16 months to 46.2% at 12 months for dasatinib. 19,39 The median time to CCyR was reported as 4.8 months in a study of ponatinib-treated patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The CCyR rate ranged from 16.1% with omacetaxine to 64.8% with ponatinib at 6 months, and the corresponding values at 12 months were 16.2% to as high as 83.9% with bosutinib. 28–31 Among the included interventions, the CCyR rates ranged from 38.7% at 6 months to 66% at 10.2 months for asciminib, 20,32 16.2% at 12 months to 83.9% at 12 months for bosutinib, 30,31 6% at 15 months to 69.6% at 40.8 months for ponatinib, 33,34 4% at 19.1 months to 16.1% at 6 months for omacetaxine, 28,35 36.8% at 12.8 months to 65.9 at 7.9 months for olverembatinib, 36,37 24% at 12 months to 31% at 16 months for nilotinib, 19,38 and 11% at 16 months to 46.2% at 12 months for dasatinib. 19,39 The median time to CCyR was reported as 4.8 months in a study of ponatinib-treated patients.…”
Section: Resultsmentioning
confidence: 99%
“…The MMR rate ranged from 10.5% with omacetaxine to as high as 66.7% with ponatinib at 6 months of follow-up and was 14–35% with ponatinib at 12 months of follow-up. 26,27,29,35,42 Among the included interventions, the MMR rates ranged from 23.3% at 6 months to 41% at 10.2 months for asciminib, 20,32 13.2% at 6 months to 76.4% at 24 months for bosutinib, 25,30 14% at 6 months to 66.7% at 6 months for ponatinib, 27,29 10.5–19.2% at 6 months for omacetaxine, 28,35 14.7% at 12.8 months to 48.8% at 7.9 months for olverembatinib, 36,37,55 13% at 16 months to 33.3% at 12 months for nilotinib, 19,22 and 20.8% at 12 months to 33.3% at 16 months for dasatinib. 19,39…”
Section: Resultsmentioning
confidence: 99%
“…However, some BCR-ABL1 or compound mutations (for example, T315M, T315V, and Y253H/T315I or E255V/T315I) can create ponatinib resistance [ 168 ]. Olverembatinib (HQP1351), a novel orally administered 3G-TKI, was found to be highly effective in CML patients who were resistant to existing TKI treatments, including some with T315I mutations in a phase II trial [ 169 ]. Vodobatinib (K0706) is another new orally bioavailable 3G-TKI with promising in vitro action against majority of BCR-ABL mutations, but not T315I.…”
Section: Therapeutic Implications Of CML Lscsmentioning
confidence: 99%
“…Additionally, preclinical studies have shown that there is synergistic activity when combining Asciminib and ponatinib [ 44 ] Olverembatinib is a third-generation BCR-ABL TKI which is highly effective in CML patients with T315I mutation. In a phase II study (CC 202) of 23 patients with CML-AP, Olverembatinib achieved a CHR of 60.9% and CCyR of 39.1% [ 45 ]. PF114 is an oral TKI similar to ponatinib and was studied in a phase I/II study of 51 patients with CP/AP CML resistant to two or more TKIs.…”
Section: Introductionmentioning
confidence: 99%
“…Olverembatinib is a third-generation BCR-ABL TKI which is highly effective in CML patients with T315I mutation. In a phase II study (CC 202) of 23 patients with CML-AP, Olverembatinib achieved a CHR of 60.9% and CCyR of 39.1% [ 45 ].…”
Section: Introductionmentioning
confidence: 99%